1997
DOI: 10.1159/000169083
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Hepatitis B Virus Associated Glomerulonephritis with Recombinant Human Alpha Interferon

Abstract: To evaluate the therapeutic effect of recombinant human α-interferon (α-IFN) on hepatitis B virus associated glomerulonephritis (HBV-GN) and the relationship between the seroconversion of viral antigens and the change of pro-teinuria, the hepatitis B viral markers and urinary protein were monitored during α-IFN treatment in 8 male adult patients who (1) were positive in serum HBsAg and HBeAg, (2) had chronic hepatitis, (3) had persistent proteinuria > 1 g/day, and (4) showed glomerulonephritis on kidney biopsy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…Antiviral therapy has been recommended in many studies for HBV-GN since it can effectively inhibit HBV replication and attenuate proteinuria [9,[25][26][27][28][29][30][31][32][33] . Our results demonstrated that antiviral therapy could significantly improve the remission rate of proteinuria, the clearance rate of HBeAg, and renal progression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Antiviral therapy has been recommended in many studies for HBV-GN since it can effectively inhibit HBV replication and attenuate proteinuria [9,[25][26][27][28][29][30][31][32][33] . Our results demonstrated that antiviral therapy could significantly improve the remission rate of proteinuria, the clearance rate of HBeAg, and renal progression.…”
Section: Discussionmentioning
confidence: 99%
“…and even immunosuppressive agents like mycophenolate mofetil, leflunomide [7,8] . It has been shown that antiviral therapy can promote the clearance of HBV and improve the coexisting renal disease [3] , but the efficacy of interferon on HBV-GN has not been confirmed [9,10] . Moreover, interferon therapy is not as successful for HBV-GN in children as for HBV-GN in adults [3] .…”
Section: Introductionmentioning
confidence: 99%
“…Treatment of HBV-associated glomerulopathy remains controversial [9,17,18,19,20,21]. It is claimed that steroids might induce the replication of HBV and prolong the persistence of liver disease or lead to acute hepatic decompensation [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported that newly diagnosed childhood nephrotic syndrome with HBs antigenemia is not a contraindication for the use of corticosteroid treatment in a slow tapering regimen combined with interferon therapy and close clinical monitoring [24]. There have been conflicting reports of interferon treatment alone of hepatitis B-associated glomerulonephritides [17,18,19,20]. Although there have been no large series suggesting a definite beneficial effect on HBVassociated nephropathy, a small group of patients may respond well to this treatment [20].…”
Section: Discussionmentioning
confidence: 99%
“…Treatment with interferon [14, 1825] or lamivudine [17, 2628] has been reported to lead to a reduction of proteinuria in patients, mostly children, with HBV-related membranous nephropathy.…”
Section: Hbv-related Glomerulonephritismentioning
confidence: 99%